2014
DOI: 10.1016/j.bpj.2014.10.061
|View full text |Cite
|
Sign up to set email alerts
|

The Motility of Axonemal Dynein Is Regulated by the Tubulin Code

Abstract: Microtubule diversity, arising from the utilization of different tubulin genes and from posttranslational modifications, regulates many cellular processes including cell division, neuronal differentiation and growth, and centriole assembly. In the case of cilia and flagella, multiple cell biological studies show that microtubule diversity is important for axonemal assembly and motility. However, it is not known whether microtubule diversity directly influences the activity of the axonemal dyneins, the motors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 49 publications
5
41
0
Order By: Relevance
“…Similar findings have been reported in vivo, where the Dynactin subunit p150 and tubulin tyrosination were shown to mediate the initiation of retrograde vesicle transport in neurons [359]. Finally, these data are in line with previous studies reporting that p150/Dynactin has higher affinity for tyrosinated microtubules [325,360] and that the motility of both cytoplasmic and axonemal Dyneins highly depends on tubulin C-terminal tails [325,361,362,363]. …”
Section: Mechanisms Of Chromosome Congressionsupporting
confidence: 89%
“…Similar findings have been reported in vivo, where the Dynactin subunit p150 and tubulin tyrosination were shown to mediate the initiation of retrograde vesicle transport in neurons [359]. Finally, these data are in line with previous studies reporting that p150/Dynactin has higher affinity for tyrosinated microtubules [325,360] and that the motility of both cytoplasmic and axonemal Dyneins highly depends on tubulin C-terminal tails [325,361,362,363]. …”
Section: Mechanisms Of Chromosome Congressionsupporting
confidence: 89%
“…28,29 The lack of glutamylation in the purified T. thermophila tubulin was surprising, given that it was a prominent tubulin PTM in Tetrahymena cells 30 and was not excluded by a TOG purification of Chlamydomonas tubulin. 31 Our relatively homogeneous population of glycylated tubulin allowed us to quantify how the conformational ensemble was affected by the presence of glycylation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed that ciliary motility is regulated by the B-microtubule modification polyglutamylation (Alper et al 2014; Ikegami et al 2010; Kubo et al 2010; Suryavanshi et al 2010) see also (Sirajuddin et al 2014). Kubo et al, (2012) proposed that dynein e and/or the N-DRC might be regulated by B-tubule polyglutamylation.…”
Section: Resultsmentioning
confidence: 99%